Afterimages of Gilles Deleuze's Film Philosophy - Rodowick, David Norman (Book collections on Project MUSE., 2010)
The French philosopher Gilles Deleuze was one of the most innovative and revolutionary thinkers of the twentieth century. Author of more than twenty books on literature, music, and the visual arts, Deleuze published the first volume of his two-volume study of film, Cinema 1: The Movement-Image, in 1983 and the second volume, Cinema 2: The Time-Image, in 1985. Since their publication, these books have had a profound impact on the study of film and philosophy. Film, media, and cultural studies scholars still grapple today with how they can most productively incorporate Deleuze's thought. The firs.